On Multinational Corporations and the Provision of Positive Rights - Parkan, Baris (Journal of business ethics, 2008)
Increased and active involvement of multinational corporations in the promotion of social welfare, in developing countries in particular, through the facilitation of partnerships and cooperation with public and nonprofit sectors, challenges the existing framework of our social and political institutions, the boundaries of nation-states, the distinction between the private and public spheres of our lives, and thus our freedom. The blurring of certain distinctions, which ought to be observed between the political and the economic is most manifest in the gradual saturation of the field of business ethics with rights-based arguments and analyses. In this article, I first argue against endorsing positive rights as having the same status as negative rights, and then try to demonstrate that, with the transportation of ‹rights talk’ into business ethics, the dangers of conflating positive and negative rights are superimposed on the dangers of conflating the private and the political. I conclude by presenting my own stance on the debate on what our basic institutionally sanctioned rights should be, and what the corresponding duties of multinational corporations really are.